Strategi pengelolaan limbah padat RSUD Provinsi X (studi kasus masa pandemi Covid-19) - Phivi Andriza; Ridwan Manda Putra; Syahril Nedi (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2023)
Regional General Hospital X is the largest hospital and referral for Covid-19 patients in one of the Province in Indonesia. The Covid-19 outbreak that has occurred since 2020 has caused an increase in the number of patients to the Regional General Hospital X. The increasing number of patients in hospitals causes an increase in the amount of hospital waste generated. The purpose of this study was to formulate a solid waste management strategy at the Regional General Hospital X which became a referral hospital for Covid-19 patients. The study was conducted by collecting secondary data in the form of medical and non-medical solid waste generation data from hospitals before and during the Covid-19 pandemic. Primary data through filling out questionnaires and in-depth interviews. The number of respondents was 34 people consisting of a sanitarian team of 4 people, 12 Pinere room nurses, 2 garbage collectors, 9 waste sorters, 6 waste processors, and 1 person from the management team, namely the Head of the Household Sub-department. The results of the study were that during the Covid-19 pandemic there was an increase in the amount of medical and non-medical solid waste. The biggest medical waste generation occurred in 2021 which was 2 times that of 2020. The obstacle in managing solid waste at the Regional General Hospital in X Province during the Covid-19 pandemic was the lack of careful human resources in following SOPs and the lack of human resources in waste collection activities. The medical solid waste management strategy uses the strength and opportunity strategy because the results of the SWOT analysis show advantages in the strengths and opportunities of the Regional General Hospital X. The strategy implemented is to improve the quality and competence of human resources for nurses and solid waste managers and improve the supporting infrastructure for medical and non-medical solid waste management.